2023
DOI: 10.1186/s12905-023-02205-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of breast cancer screening in the overdiagnosis of thyroid cancer: results from a cross-sectional nationwide survey

Abstract: Background South Korea has the highest incidence of thyroid cancer worldwide, raising questions regarding the possibility of overdiagnosis. Examining the factors affecting thyroid cancer screening is crucial in elucidating the reasons for this unusually high incidence of thyroid cancer. Therefore, in the present study, we investigated the association between breast cancer screening and thyroid cancer screening to determine the potential role of breast cancer screening in the overdiagnosis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A nationwide survey in Korea reported that breast ultrasonography was performed extensively in women. A total of 42.1% of women aged 30 years or older received breast ultrasound and of those who received breast cancer screening, more than 50% had received breast ultrasound . In this study, we were unable to identify whether women in the high-density category received additional supplemental screening; however, considering that breast ultrasound is widely performed in Korea, it could be expected that a higher proportion of women with dense breasts would undergo additional breast ultrasound examinations, which presents an inverse association between the increase in density category and decrease in IBC.…”
Section: Discussionmentioning
confidence: 88%
“…A nationwide survey in Korea reported that breast ultrasonography was performed extensively in women. A total of 42.1% of women aged 30 years or older received breast ultrasound and of those who received breast cancer screening, more than 50% had received breast ultrasound . In this study, we were unable to identify whether women in the high-density category received additional supplemental screening; however, considering that breast ultrasound is widely performed in Korea, it could be expected that a higher proportion of women with dense breasts would undergo additional breast ultrasound examinations, which presents an inverse association between the increase in density category and decrease in IBC.…”
Section: Discussionmentioning
confidence: 88%